Effects of Aripiprazole on Olanzapine Population Pharmacokinetics and Initial Dosage Optimization in Schizophrenia Patients - Zhang C; Jiang L; Hu K; Chen L; Zhang YJ; Shi HZ; He SM; Chen X; Wang DD (Neuropsychiatric Disease and Treatment, 2024)
Cun Zhang,1,* Lei Jiang,2,3,* Ke Hu,2,* Liang Chen,2 Yi-Jia Zhang,2 Hao-Zhe Shi,2 Su-Mei He,4 Xiao Chen,5 Dong-Dong Wang2 1Department of Pharmacy, Xuzhou Oriental Hospital Affiliated to Xuzhou Medical University, Xuzhou, Jiangsu, 221004, People’s Republic of China; 2Jiangsu Key Laboratory of New Drug Research and Clinical Pharmacy & School of Pharmacy, Xuzhou Medical University, Xuzhou, Jiangsu, 221004, People’s Republic of China; 3Department of Pharmacy, Taixing People’s Hospital, Taixing, Jiangsu, 225400, People’s Republic of China; 4Department of Pharmacy, Suzhou Hospital, Affiliated Hospital of Medical School, Nanjing University, Suzhou, Jiangsu, 215153, People’s Republic of China; 5School of Nursing, Xuzhou Medical University, Xuzhou, Jiangsu, 221004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Su-Mei He, Department of Pharmacy, Suzhou Hospital, Affiliated Hospital of Medical School, Nanjing University, No. 1 Lijiang Road, Suzhou, Jiangsu, 215153, People’s Republic of China, Email hehe8204@163.com Dong-Dong Wang, Jiangsu Key Laboratory of New Drug Research and Clinical Pharmacy & School of Pharmacy, Xuzhou Medical University, No. 209 Tongshan Road, Xuzhou, Jiangsu, 221004, People’s Republic of China, Email 13852029591@163.comObjective: Olanzapine has already been used to treat schizophrenia patients; however, the initial dosage recommendation when multiple drugs are used in combination, remains unclear. The purpose of this study was to explore the drug–drug interaction (DDI) of multiple drugs combined with olanzapine and to recommend the optimal administration of olanzapine in schizophrenia patients.Methods: In this study, we obtained olanzapine concentrations from therapeutic drug monitoring (TDM) database. In addition, related medical information, such as physiological, biochemical indexes, and concomitant drugs was acquired using medical log. Sixty-five schizophrenia patients were enrollmented for analysis using population pharmacokinetic model by means of nonlinear mixed effect (NONMEM).Results: Weight and combined use of aripiprazole significantly affected olanzapine clearance. Without aripiprazole, for once-daily olanzapine administration dosages, 0.6, 0.5 mg/kg/day were recommended for 40– 70, and 70– 100 kg schizophrenia patients, respectively; for twice-daily olanzapine administration dosages, 0.6, 0.5 mg/kg/day were recommended for 40– 60, and 60– 100 kg schizophrenia patients, respectively. With aripiprazole, for once-daily olanzapine administration dosages, 0.4, 0.3 mg/kg/day were recommended for 40– 53, and 53– 100 kg schizophrenia patients, respectively; for twice-daily olanzapine administration dosages, 0.4 mg/kg/day was recommended for 40– 100 kg schizophrenia patients, respectively.Conclusion: Aripiprazole significantly affected olanzapine clearance, and when schizophrenia patients use aripiprazole, the olanzapine dosages need adjust. Meanwhile, we firstly recommended the optimal initial dosages of olanzapine in schizophrenia patients.Keywords: aripiprazole, olanzapine, population pharmacokinetics, initial dosage optimization, schizophrenia patients